Cálculo e análise do fator de amplificação dinâmica em içamentos off-shore não submersos utilizando balsas guindaste, com foco em descomissionamento de plataformas de petróleo - Cúnico, Moisés Negri (2018)
The decommissioning of oil platforms is a growing market that already accounts for a large share of the costs involved in the offshore industry, with the optimization of lifting operations being one of the ways to reduce such costs. This work presents a methodology for calculating the dynamic amplification during a non-submerged lifting operation (focusing on fixed platforms decks) for a crane barge. It is proposed a mathematical model based on Potential Theory, together with an experimentally adjusted value for the non-linear damping in Roll motion. The value of the calculated amplification is then compared with the value measured in a real lifting operation of a fixed platform deck, and later with the value recommended by the design standards. The results indicate the possibility of reducing the normative factor for operations of this nature.